THE ROLE OF FINTECH IN ENHANCING FINANCIAL INCLUSION AND ECONOMIC GROWTH IN EMERGING MARKETS: A CASE STUDY OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2024)
The rapid growth of financial technology (fintech) has reshaped the financial services sector globally, with emerging markets experiencing significant transformations in financial inclusion and economic development. This paper examines the impact of fintech on financial inclusion and economic growth in Uzbekistan using empirical data and case study analysis. The study evaluates how fintech innovations, such as digital payment platforms, microfinance services, and blockchain technology, have increased access to financial services, supported the growth of small and medium-sized enterprises (SMEs), and contributed to the country’s economic modernization. The findings highlight the challenges and opportunities faced by fintech providers and policymakers, suggesting strategies for fostering a more inclusive and sustainable financial ecosystem. Recommendations for addressing regulatory and infrastructural challenges are also provided.